What is the relationship between inspiratory muscle training and performance and respiratory biomechanics in athletes? - Santos, José (2023)
Inspiratory muscle training has an important role in sports performance. Scientific evidence suggests the coadjuvation of sports performance competition training with association of training of the inspiratory muscles alongside the use of a threshold. The purpose of this review is to summarize and assess the scientific evidence about optimizing respiratory biomechanics in specific sports.